LARYNGOTRACHEAL FOREIGN BODIES IN MAIDUGURI: A TEN YEAR REVIEW - HI GARANDAWA; A ISA; BM AHMAD (Kanem Journal of Medical Sciences, 2001)
Background: Foreign body impaction in the larngotracheal tree, a major cause of upper airway obstruction in children, is an otorhinolaryngological emergency. Direct laryngoscopy, tracheoscopy or bronchoscopy is usually employed to remove foreign body in the upper airway. However, tracheostomy may be required to secure the airway before endoscopic removal is carried out in some cases. Objective: To determine the prevalence of laryngotracheal foreign body in our community and highlight the life threatening consequences when referrals are delayed. Method: This is a retrospective evaluation of case records of 44 patients who presented with history of foreign body inhalation or features of upper airway obstruction between January 1995 and December 2004 at the University of Maiduguri Teaching Hospital. Results: A total of 44 patients were found to have foreign body impaction over the study period. Sixty eight point two percent were males and 31.8% females. Children under 4 years of age were mostly affected constituting 61.4%. The commonest type of foreign body inhaled was bean seed constituting 27.2%. Ninety point nine percent of the patients had endoscopic removal of foreign body and 37.5% had emergency tracheostomy to secure the airways pre-operatively. Conclusion: Foreign body inhalation could be life threatening hence children below the age of 4years should not be allowed to play with small toys unattended to, or be allowed to play close to beans or groundnut drying fields as is the case in some farming communities.